Hallowed stewards : Solon and the sacred treasurers of ancient Athens - Bubelis, William Stanley (Societas : historical studies in classical culture, 2014)
"Students of ancient Athenian politics, governance, and religion have long stumbled over the rich evidence of inscriptions and literary texts that document the Athenians' stewardship of the wealth of the gods. Likewise, Athens was well known for devoting public energy and funds to all matters of ritual, ranging from the building of temples to major religious sacrifices. Yet, lacking any adequate account of how the Athenians organized that commitment, much less how it arose and developed, ancient historians and philologists alike have labored with only a paltry understanding of what was a central concern to the Athenians themselves. That deficit of knowledge, in turn, has constrained and diminished our grasp of other essential questions surrounding Athenian society and its history, such as the nature of political life in archaic Athens, and the forces underlying Athens' imperial finances. Hallowed Stewards closely examines those magistracies that were central to Athenian religious efforts, and which are best described as "sacred treasurers." Given the extensive but nevertheless fragmentary evidence now available to us, no catalog-like approach to these offices could properly encompass their details much less their wider historical significance. Inscriptions and oratory provide the bulk of the evidence for this project, along with the so-called Constitution of Athens attributed to Aristotle. Hallowed Stewards not only provides a wealth of detail concerning these hitherto badly understood offices, but also the larger diachronic framework within which they operated"--